Gestures and Their Meanings of Main Character in Daniel’s Movie Everything Everywhere All at Once (2022) - Fauziah Khairani Lubis; Syamsul Bahri (RIRAI Publisher, 2023)
Gesture is a unique nonverbal communication signal, whereby a person conveys a message or expresses himself through conscious or unconscious movements, body movements, and facial expressions